Fintech Adoption for SME Development: Perceived Usefulness and Ease of Use: Pengaruh Persepsi Kebermanfaatan dan Kemudahan Penggunaan terhadap Adopsi Fintech untuk Pengembangan UMKM: Bukti dari Sidoarjo - Fitriah Sukandar; Sigit Hermawan (Academia Open, 2022)
This study examines the impact of perceived usefulness and ease of use on the adoption of financial technology (fintech) for the advancement of small and medium enterprises (SMEs) in Sidoarjo. Employing a purposive sampling technique, data was collected from 100 respondents using primary sources. Multiple linear regression analysis was conducted with SPSS 25 to analyze the data. The findings reveal that perceived usefulness significantly influences fintech adoption, while the perception of ease of use also plays a significant role. These results underscore the importance of enhancing the perceived value and ease of utilization of fintech solutions in promoting their adoption among SMEs. The study's implications emphasize the need for policymakers, financial institutions, and technology providers to focus on designing user-friendly fintech platforms and enhancing their perceived value to foster SME development and growth. Highlights: Fintech adoption drives SME development: This study examines the impact of perceived usefulness and ease of use on the adoption of financial technology (fintech) by small and medium enterprises (SMEs). It explores how fintech adoption can contribute to the growth and development of SMEs. Perceived usefulness influences fintech adoption: The findings indicate that SMEs are more likely to adopt fintech when they perceive it as beneficial. Understanding the perceived usefulness of fintech solutions is crucial for encouraging their adoption and potential benefits for SMEs. Ease of use facilitates fintech adoption: The study reveals that the perception of ease of use has a positive impact on fintech adoption. Enhancing the user-friendliness of fintech solutions can play a significant role in increasing their adoption rates among SMEs, enabling them to leverage the benefits of digital financial services. Keywords: Fintech adoption, SME development, Perceived usefulness, Ease of use, Sidoarjo